(untitled) (Global Journal of Management and Business Research, 2013)
Turkey harbours one of the greatest untapped microfinance markets in the world. Despite its enormous dormant potential, few studies were undertaken in order to potrait the socio-economic character of its main protagonist: enterprising mother operating in the suburbs of urban and semi-urban environment. The study summarizes result of field research carried out by team of researchers from Czech University of Life Sciences and models a credit mannequin, profiling the average Turkish microfinance client in suburban areas of Central Anatolia. The assemblage enables to depict genuine relationships of mainstream clientele towards selected topics, reaching better understanding of nature and particularities of the Turkish microfinance market and drawing conclusions on its further development.